1984
DOI: 10.1159/000260793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Oral Microbial Flora of Caries-Free Humans and Conventional Sprague-Dawley Rats

Abstract: In this study, the bacteria from molar dental plaque and scrapings of the tongue of 12 conventional Sprague-Dawley rats on a diet of Purina Rodent Laboratory Chow No. 5001 and tap water were identified at the species or genus level quantitated using anaerobic culture techniques and selected biochemical tests. These results were compared to the microbial composition of dental plaque and scrapings from dental and tongue sites, evaluated by similar cultural techniques, of 7 caries-free students on a low-sugar die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…The low recovery of Gram-negative cocci (Veillonella and Neisseria species) has been explained in other animal models by their poor adherence to oral surfaces and pre-formed dental plaque (Liljemark and Gibbons, 1971;Hall et al, 1984). Anaerobic Gram-positive rods of the oral flora in man were not identified in baboons.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The low recovery of Gram-negative cocci (Veillonella and Neisseria species) has been explained in other animal models by their poor adherence to oral surfaces and pre-formed dental plaque (Liljemark and Gibbons, 1971;Hall et al, 1984). Anaerobic Gram-positive rods of the oral flora in man were not identified in baboons.…”
Section: Resultsmentioning
confidence: 98%
“…The facultative anaerobic members were Escherichia coli, Klebsiella ozaenae, and Citrobacter freundii. All have been identified as dominant species of the Gram-negative bacilli in rats (Rosebury et al, 1934;Hall et al, 1984), but are infrequently found in humans (Hardie, 1976). Among the Gram-positive cocci, the cariogenic mannitol-positive S. mutans (serotype h) was isolated.…”
Section: Resultsmentioning
confidence: 99%
“…When a cariogenic diet was used, the rats' general health was affected in many ways, as follows15,16): (1) the molar teeth were smaller and weighed less than normal, (2) incisor teeth lost the usual orange pigmentation and the mandibule and femur were smaller in size than normal, (3) the weight gained was less than normal, (4) protein-calorie levels in the bones and teeth of the rats were deficient. Studies using animal models are necessary and effective, for human caries research Hall et al 22) investigated similarities of oral microflora. It is suggested that a strain of rats with naturally occurring dental caries is a more appropriate model to research on human dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…ΠοΧΧά σχελέχη στρεπτόκοκκων μπορούν να μεχαβολίσουν χη σουκρόζη, Ο Str. mutans, όμιυς, αποτελεί τον πλέον χερηδονογόνο μικροοργανισμό της πλάκας και είναι εξαρτώμενος από χη σουκρόζη (Hamada & Slade, 1980;Loesche, 1985).…”
Section: ί1) σουκρόζη και μικροβιακή πλάκαunclassified
“…από όλες τις άλλες, εξακολουθώντας όμως να είναι σε χαμηλό επίπεδο και πολύ κοντά, στο ποσοστό των Str. mutans της φυσιολογικής χλωρίδας των επιμϋων (Hall et al, 1984). Ενδει κτικά αναφέρουμε οτι η διατροφή με 56/.…”
Section: C-i Inunclassified